Deciphering transplant outcomes of expanded kidney allografts donated after controlled circulatory death in the current transplant era. A call for caution. (28th October 2021) - Montero, Nuria; Toapanta, Néstor; Pallarès, Natàlia; Crespo, Marta; Diekmann, Fritz; Guirado, Lluis; Esteban, Rafael; Codina, Sergi; Melilli, Edoardo; Buxeda, Anna; Velis, Gonzalo; Torres, Irina B.; et al.
Summary: Outcomes of kidney transplantation (KT) after controlled circulatory death (cDCD) with highly expanded criteria donors (ECD) and recipients have not been thoroughly evaluated. We analyzed in a multicenter cohort of 1161 consecutive KT, granular baseline donor and recipient factors predicting transplant outcomes, selected by bootstrapping and Cox proportional hazards, and were validated in a contemporaneous European KT cohort ( n = 1585). 74.3% were DBD and 25.7% cDCD‐KT. ECD‐KT showed the poorest graft survival rates, irrespective of cDCD or DBD (log‐rank < 0.001). Besides standard ECD classification, dialysis vintage, older age, and previous cardiovascular recipient events together with low class‐II‐HLA match, long cold ischemia time and combining a diabetic donor with a cDCD predicted graft loss (C‐Index 0.715, 95% CI 0.675–0.755). External validation showed good prediction accuracy (C‐Index 0.697, 95%CI 0.643–0.741). Recipient older age, male gender, dialysis vintage, previous cardiovascular events, and receiving a cDCD independently predicted patient death. Benefit/risk assessment of undergoing KT was compared with concurrent waitlisted candidates, and despite the fact that undergoing KT outperformed remaining waitlisted, remarkably high mortality rates were predicted if KT was undertaken under the worst risk‐prediction model. Strategies to increase the donor pool, including cDCD transplants with highly expanded donor and recipient candidates, should be performed with caution. Abstract : This study presents two prediction models for graft and patient survival using granular data. Even in the worst risk‐prediction scenario, KT seems to provide better patient survival expectancy as compared with remaining on the waiting list but with a high mortality risk if this high‐risk kidney transplantation is undertaken.